2006
DOI: 10.1016/j.chembiol.2006.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Specific Arabinosyltransferase Activity Involved in Mycobacterial Arabinan Biosynthesis

Abstract: Mycobacterium smegmatis strains that contain inactivated EmbA or EmbB proteins are unable to synthesize terminal Arabeta1-->2Araalpha1-->5(Arabeta1-->2Araalpha1-->3)Araalpha1-->5Araalpha1-->(Ara(6)) motif in the cell wall polysaccharide arabinogalactan. Instead, the mutants contain a linear Arabeta1-->2Araalpha1-->5Araalpha1-->5Araalpha1-->(Ara(4)) motif, suggesting that these proteins are involved in the synthesis or transfer of the disaccharide Arabeta1-->2Araalpha1--> to an internal 5-linked Ara. Therefore,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
50
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(55 citation statements)
references
References 34 publications
3
50
2
Order By: Relevance
“…We and others have previously evaluated the effectiveness of several synthetic neoglycolipids as substrates for mycobacterial glycosyltransferase activities 11, 12 . Specifically, di- and trimannosides with an octyl aglycon chain (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We and others have previously evaluated the effectiveness of several synthetic neoglycolipids as substrates for mycobacterial glycosyltransferase activities 11, 12 . Specifically, di- and trimannosides with an octyl aglycon chain (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Enzymes which incorporate and polymerize the arabinan, the arabinofuranosyltransferases (Aft), are potential targets for an anti-tuberculosis drug-development [32,[117][118][119]. The arabinofuranose (Araf ) motif, is a biologically rare sugar.…”
Section: Arabinosyltransferases (Arats) As Anti-tuberculosis Drug Tarmentioning
confidence: 99%
“…These studies elucidate the contributions of EmbA and EmbB in the formation of the terminal hexaarabinofuranosyl (Ara 6 ) (Fig. 18.9) assembly by catalyzing the transfer of the β-d-Araf-(1→2)-α-d-Araf disaccharide to the AG[119,129]. Analogous studies on the inactivation ofFigure 18.9 Terminating residue of arabinofuranosyl hexasaccharide.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…It is synthesized from 5-phosphoribose-1-pyrophosphate (Scherman et al ., 1995; Scherman et al ., 1996) - the product of the phosphoribosyl-pyrophosphate synthetase PrsA (Alderwick et al ., 2011a) - through four reaction steps involving the Dec-P 5-phosphoribosyltransferase, UbiA (Rv3806c) (Huang et al ., 2005; Huang et al ., 2008; Alderwick et al ., 2005), the phosphoribosyl-monophosphodecaprenol phosphatase Rv3807c (Jiang et al ., 2011), and DprE1 (Rv3790) and DprE2 (Rv3791) responsible for the epimerization of decaprenyl-phosphate ribose to Dec-P-Ara (Mikušová et al ., 2005). The AraTs involved in the formation of the arabinan domain of AG identified to date include AftA (Rv3792), responsible for the transfer of the very first Ara f residues to the galactan domain of AG (Alderwick et al ., 2006a), the terminal β–(1,2)-capping AraT AftB (Rv3805c) (Seidel et al ., 2007), AftC (Rv2673) involved in the internal α–(1,3)-branching of AG (Birch et al ., 2008) and the EmbA (Rv3794) and EmbB (Rv3795) proteins involved in the formation of the Ara 6 motif of AG (Escuyer et al ., 2001; Khasnobis et al ., 2006). We successfully overexpressed and purified a soluble form of AftC from M. smegmatis and showed that it retains α–(1,3)-branching AraT activity in vitro upon reconstitution into proteoliposomes containing mycobacterial lipids (Zhang et al ., 2011).…”
Section: The Major Cell Envelope Glycoconjugates Of Mtbmentioning
confidence: 99%